Reseeding promotes plant biomass by improving microbial community stability and soil fertility in a degraded subalpine grassland - Debao Li; Sicheng Li; Hao Chen; Jianping Wu (Geoderma)
Forage monoculture and grass-legume mixtures are popular reseeding practices in degraded grasslands. However, the mechanism understanding for the effect of multiple reseeding approaches on soil microbial community and their associated ecosystem functioning remains unclear. Here, we conducted a 3-year field reseeding experiment with eight treatments in a degraded grassland in southern China to test how the link between plant biomass and soil microbial community stability are influenced by plant community structure. Assessments of both above- and below-ground characteristics revealed that reseeding significantly improved plant biomass, soil fertility, and community stability by 53.96 %-126.32 %, 40.74 %-106.91 %, and 13.97 %–33.17 % (P < 0.05) on average, respectively. Furthermore, we found that plant biomass, soil fertility, and microbial community stability increased with increasing number of reseeding species. Dactylis glomerata, Trifolium repens and Lolium perenne mixed-reseeding had significantly higher plant biomass, soil fertility, and microbial community stability than monocultures (P < 0.05). Microbial community stability was positively correlated with plant biomass (P < 0.001). Our field work demonstrates that grass-legume mixtures are beneficial for plant biomass and soil microbes, where stable microbial communities are essential for maintaining ecosystem functions. As such, our findings provide new evidence to guide reseeding practices in degraded southern grasslands and offer novel theoretical insights into plant-soil-microbe interactions under grass-legume mixtures reseeding.